2021
DOI: 10.2147/opth.s266123
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Smartphone Funduscopy with 20 Diopter Lens in Undergraduate Medical Education

Abstract: To assess attitudes of pre-clinical undergraduate medical students toward learning smartphone funduscopy (SF) and its appropriateness as a teaching tool. Patients and Methods: Second year medical students received instruction on direct ophthalmoscopy (DO) and SF; they were then paired with a peer and randomly assigned to perform DO or SF first. The SF technique involved freehand alignment of the axes of the smartphone camera with a condenser lens. Both techniques were done through a maximally dilated pupil. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Use of smartphone technology to evaluate the retinal AV dimension has been available for many years, but is not frequently done as it is labour intensive. 20 , 21 In the present study we performed video recording of retinal image with minimal discomfort to the patient and selected the most suitable image from the recorded image. The technology is simpler, quicker to learn, less invasive, has high patient compliance, observation of a larger retinal field at any one time is possible compared with routine ophthalmoscopy, pupillary dilation may not be required (although we used pupillary dilatation in all our patients), images can be saved for review later, and progression of disease can be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Use of smartphone technology to evaluate the retinal AV dimension has been available for many years, but is not frequently done as it is labour intensive. 20 , 21 In the present study we performed video recording of retinal image with minimal discomfort to the patient and selected the most suitable image from the recorded image. The technology is simpler, quicker to learn, less invasive, has high patient compliance, observation of a larger retinal field at any one time is possible compared with routine ophthalmoscopy, pupillary dilation may not be required (although we used pupillary dilatation in all our patients), images can be saved for review later, and progression of disease can be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MS preferred the new device than the traditional one (78.2 % vs. 77.2 %, p < 0.0001). However, a study that compared CO to a 20 diopters lens plus smartphone camera [ 31 ] in identify the optic nerve head, macula and retina vessels found a different outcome. Among 137 MS enrolled for the 20 to 25-minute instruction in one device or another, they referred a higher quality of visualization of optic nerve head and macula in CO than in the SF, with less attempts need to identify the structures with CO (2.7 ± 2.3 vs. 4.5 ± 2.9, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in 2021, Kohler et al investigated this method and concluded that it is not inferior to direct ophthalmoscopy for identifying the structures of the eye fundus, even suggesting that it could be incorporated into undergraduate medical education. 24 …”
Section: Methodsmentioning
confidence: 99%
“…Recently, in 2021, Kohler et al investigated this method and concluded that it is not inferior to direct ophthalmoscopy for identifying the structures of the eye fundus, even suggesting that it could be incorporated into undergraduate medical education. 24 Besides being relatively easy to perform and cost-effective, smartphone assisted indirect ophthalmoscopy using condensing lenses easily results in images that are suitable for remote expert assessment, that is to say, the practicing of telemedicine in the evaluation of the retina and optic disc. In social programs working in remote areas, where there is a lack of medical specialists or where non-portable devices such as retinographics are unavailable, obtaining fundus images from cell phones and sharing them with specialists allows for better evaluation and more complete therapeutic planning, even when a specialist cannot be present on site.…”
Section: Fundoscopy Using Smartphonesmentioning
confidence: 99%